Shear strength of reinforced concrete beams with T-headed bars for safety-related nuclear structures. (1st March 2021) - Yang, Yuxing; Varma, Amit H.; Kreger, Michael E.; Wang, Ying; Zhang, Kai
Highlights: Investigates the shear behavior of RC beams with T-headed bars. Conducts 12 cyclic tests on RC beams. Evaluates the influences of three test parameters. Evaluates design codes from six countries. Abstract: Excessive amounts of longitudinal and transverse reinforcement are required in concrete structures for safety-related nuclear structures to satisfy design and safety regulations. Closely spaced conventional single-leg stirrups are required for seismic detailing. These requirements lead to rebar congestion, difficulties in installation, and delay in the construction period. To solve these problems, it was proposed to use T-headed bars to replace the single-leg stirrups in this paper. A total of 12 tests were conducted to evaluate the effectiveness of using T-headed bars as shear reinforcement. The test parameters included height of beam, type of shear reinforcement (T-headed bars or stirrups), and shear span-to-depth ratio. It was shown from the test results that specimens with T-headed bars developed higher shear strength compared with specimens with conventional single-leg stirrups, while the behavior of these two types of specimens was similar. Design codes from six countries were then evaluated. It was concluded that these codes could provide conservative estimates of the shear strength for specimens with T-headed bars.